Blue space quality, quantity, and happiness in China: integrating subjective perceptions and objective indicators in a multilevel analysis - Yu, Fuxiang; Lu, Chuntian; Guo, Zhengbing (Frontiers in Psychology, 2026)
IntroductionHuman wellbeing is closely linked to interactions with natural environments, yet research on blue space has primarily focused on proximity to water bodies, paying limited attention to ecological quality, resource sufficiency, and the integration of subjective perceptions with objective conditions.MethodsThis study examines how both subjective and objective dimensions of blue space influence individual happiness in China. We used data from the 2021 Chinese General Social Survey, linked with provincial-level ecological indicators from the China Statistical Yearbook. Multilevel ordered logistic regression models were applied to assess the associations between blue space indicators and happiness, with particular attention to cross-level interactions.ResultsThe results show that blue space quality and quantity contribute to happiness in distinct ways. At the individual level, more favorable perceptions of water quality and water sufficiency are associated with higher happiness. At the provincial level, higher wastewater treatment rates and greater groundwater supply are positively associated with happiness, whereas higher ammonia nitrogen emissions and excessive surface water resources are negatively associated. Cross-level analyses further indicate that the positive effect of perceived water quality on happiness weakens in provinces with higher levels of pollution.DiscussionThese findings extend the Biophilia Hypothesis by demonstrating that, in addition to green spaces, contact with blue spaces enhances happiness through both subjective perceptions and objective environmental conditions. The results highlight the importance of sustainable water resource management for maximizing the social benefits of blue space.